Development and characterization of a nut-based beverage of Brazil nut (Bertholletia excelsa) and macadamia (Macadamia integrifolia) - MACHADO, André Luiz Borges; SILVA, Kamilla Soares; MIRANDA, Bruna Melo; CARDOSO, Cláudio Fernandes; SILVA, Flávio Alves da; FREITAS, Fernanda Ferreira (Food Science and Technology, 2024)
Brazil nuts and macadamia nuts are highly nutritious and can be used for the production of plant-based beverages. Considering the need to develop new beverages alternative to cow milk, the aim of this study was to develop water-soluble extracts based on Brazil nuts and macadamia nuts using an experimental design for simplex centroid mixtures in order to evaluate the proximate composition of the ternary mixture. The best beverage formulation was established based on sensory acceptance and shelf life, which was determined through microbiological aspects during refrigerated storage. The most accepted formulation consisted of 60% (w/w) of water, 20% (w/w) of Brazil nuts, and 20% (w/w) of macadamia nuts. The nut-based beverage presented a yellow–white color, and it was in accordance with the microbiological standards established by the Brazilian legislation, with an estimated shelf life of 28 days.